Growing Up Gay in Urban India A Critical Psychosocial Perspective - Ranade, Ketki (Springer Singapore, 2018)
This book explores the growing up experiences of gay and lesbian individuals within their homes, schools, neighbourhoods, among friends; and their journeys of finding themselves and their communities while living in a heterosexually constructed society. It is based on an exploratory, qualitative study with young gay and lesbian persons in two cities of Maharashtra, India and employs a life course perspective. The author has written this book from two primary loci: those of a mental health professional and activist, and a queer feminist activist. Through layered narratives and psychosocial analyses of experiences that are simultaneously attentive to subjectivities and to social and interpersonal processes, the author provides insights into the lives of children who grow up feeling 'different' from their siblings, peers and friends, and receive constant messages about correct ways of being and expression from their parents, teachers, friends and counsellors/doctors; the unique challenges to growing up as gay or lesbian, alongside complex processes involved in the decision of 'coming out'; and the experience of meeting others like oneself, forming intimate, romantic relationships, bonds of friendship, political solidarity, families of choice and so on. In this book, the author employs a critical stance towards mainstream life span development studies, developmental psychology, child development and childhood studies that make universal assumptions of heteronormativity and gender binarism. This book is of interest to a wide readership, from psychologists, mental health and human rights scholars, to scholars of youth and childhood studies, gender studies, cultural studies, social work, sociology and anthropology. .